2015
DOI: 10.1038/jhh.2014.124
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension outcomes in metabolically unhealthy normal-weight and metabolically healthy obese children and adolescents

Abstract: Metabolically healthy obesity (MHO) begins in childhood and continues into adulthood. However, the association between MHO and the risk of developing hypertension remains controversial. A prospective cohort study was conducted to investigate the risk of hypertension in MHO and metabolically unhealthy normal-weight (MUNW) Chinese children and adolescents. A total of 1183 participants, 6-18 years old at baseline with normal blood pressure values, were studied using follow-up data from the cohort of the Beijing C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 31 publications
5
46
0
5
Order By: Relevance
“…For instance, a recent study examining Chinese children and adolescents aged 6–18 years found that prevalence rates were 3.9 and 36.7% using 2 different MHO criteria defined by insulin resistance and cardiometabolic parameters, respectively [37]. Using the same MHO criteria as in the present study, a recently published German study on the effect of pubertal status revealed that a large proportion of obese children (49.3%) exhibited a MHO status [38].…”
Section: Discussionmentioning
confidence: 88%
“…For instance, a recent study examining Chinese children and adolescents aged 6–18 years found that prevalence rates were 3.9 and 36.7% using 2 different MHO criteria defined by insulin resistance and cardiometabolic parameters, respectively [37]. Using the same MHO criteria as in the present study, a recently published German study on the effect of pubertal status revealed that a large proportion of obese children (49.3%) exhibited a MHO status [38].…”
Section: Discussionmentioning
confidence: 88%
“…MHNO subjects; Table ). Although hypertension is one of the most important predictors of CVD mortality, few studies investigated the association between the MHO phenotype and the risk of incident hypertension . A Korean prospective study reported that the MHO phenotype defined by ATP‐III criteria was associated with a higher risk of incident hypertension, and a Chinese study group reported similar findings in MHO children and adolescents .…”
Section: Discussionmentioning
confidence: 99%
“…Because hypertension is one of the most important predictors of CVD mortality, an investigation of the association between each obesity phenotype and incident hypertension might resolve this controversy. However, few studies have investigated the association between incident hypertension and different obesity phenotypes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have concluded that MHO phenotypes are not protected against hypertension; however, one of these studies enrolled only children and adolescents in China [49] and the other involved a relatively small number of subjects [26]. We recently demonstrated that individuals with MHO had an approximately 1.5-fold higher association with the incidence of hypertension over a relatively short period of time (median follow-up period, 35.0 months), regardless of the definition used for metabolic health (i.e., NCEP-ATP III, Wildman, Karelis, and HOMA criteria) [50].…”
Section: Does Mho Have a Favorable Prognosis?mentioning
confidence: 99%